Sympatry drives colour and song evolution in wood-warblers (Parulidae) - Simpson, Richard K; Wilson, David R; Mistakidis, Allison F; Mennill, Daniel J; Doucet, Stéphanie M (Proceedings of the Royal Society. B, Biological sciences, 2021)
Closely related species often exhibit similarities in appearance and behaviour, yet when related species exist in sympatry, signals may diverge to enhance species recognition. Prior comparative studies provided mixed support for this hypothesis, but the relationship between sympatry and signal divergence is likely nonlinear. Constraints on signal diversity may limit signal divergence, especially when large numbers of species are sympatric. We tested the effect of sympatric overlap on plumage colour and song divergence in wood-warblers (Parulidae), a speciose group with diverse visual and vocal signals. We also tested how number of sympatric species influences signal divergence. Allopatric species pairs had overall greater plumage and song divergence compared to sympatric species pairs. However, among sympatric species pairs, plumage divergence positively related to the degree of sympatric overlap in males and females, while male song bandwidth and syllable rate divergence negatively related to sympatric overlap. In addition, as the number of species in sympatry increased, average signal divergence among sympatric species decreased, which is likely due to constraints on warbler perceptual space and signal diversity. Our findings reveal that sympatry influences signal evolution in warblers, though not always as predicted, and that number of sympatric species can limit sympatry's influence on signal evolution.